Maxillary dental and skeletal effects after treatment with self-ligating appliance and miniscrew-assisted rapid maxillary expansion - Calil, Roberta Caetano; Marin Ramirez, Cecilia Maria; Otazu, Aldo; Torres, Dino Marcelo; Gurgel, Júlio de Araújo [UNESP]; Oliveira, Renata Cristina; de Oliveira, Ricardo Cesar Gobbi; Valarelli, Fabricio Pinelli; Freitas, Karina Maria Salvatore (My University, 2021)
Introduction: The objective of the present study was to compare the maxillary dental and skeletal effects after treatment with self-ligating appliance and miniscrew-assisted rapid maxillary expansion (MARPE). Methods: The sample comprised 37 patients with Class I malocclusion treated without tooth extraction, divided into 2 groups: group 1 comprises 21 patients with a mean age of 19.55 years (standard deviation = 1.31), submitted to orthodontic treatment with Damon self-ligating appliance, and evaluated until the end of the alignment and leveling stage. Group 2 comprises 16 patients with a mean age of 24.92 years (standard deviation = 7.60), with maxillary atresia, who underwent MARPE, and were evaluated after the removal of the expander. Buccal bone thickness; dental inclinations; and transverse distances of the maxillary arch, nasal base, and jugula widths were measured on cone-beam computed tomography scans before and after treatment. The intergroup comparison was performed with the independent t test. Results: With treatment, there was a significantly greater decrease in buccal bone thickness of canines and premolars in the self-ligating group, the premolars presented a greater buccal inclination in the self-ligating group, and the intercanine and intermolar distances and nasal base and jugula widths showed significantly greater increases in the MARPE group than in the self-ligating group. Conclusions: MARPE treated more severe skeletal transverse maxillary discrepancies and obtained better results than self-ligating appliances in terms of buccal bone loss, tooth inclination, and transverse skeletal increase of the maxilla. MARPE presented more skeletal effects and self-ligating appliances, more dental effects.